2022
DOI: 10.4269/ajtmh.21-0849
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity of Oxford-AstraZeneca COVID-19 Vaccine in Vietnamese Health-Care Workers

Abstract: We studied the immunogenicity of the Oxford-AstraZeneca vaccine in health-care workers of a major infectious diseases hospital in Vietnam. We measured neutralizing antibodies before and 14 days after each dose, and at day 28 and month 3 after dose 1. A total of 554 workers (136 men and 418 women; age range, 22–71 years; median age, 36 years) participated with the study. Of the 144 participants selected for follow-up after dose 1, 104 and 94 gave blood for antibody measurement at weeks 6 and 8, and at month 3 a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…However, such roles remain largely uninvestigated for SARS-CoV-2 (65). However virus neutralization is one of the main mechanisms by which COVID-19 vaccines work (67)(68), and may be more likely to offer sterile immunity compared to other antibody mediated mechanisms. Understanding antibody kinetics, both quantities and functions will be important in informing current vaccination strategies, and in the development of second generation COVID-19 vaccines that could offer sterile immunity, and the much-needed long term protection.…”
Section: Discussionmentioning
confidence: 99%
“…However, such roles remain largely uninvestigated for SARS-CoV-2 (65). However virus neutralization is one of the main mechanisms by which COVID-19 vaccines work (67)(68), and may be more likely to offer sterile immunity compared to other antibody mediated mechanisms. Understanding antibody kinetics, both quantities and functions will be important in informing current vaccination strategies, and in the development of second generation COVID-19 vaccines that could offer sterile immunity, and the much-needed long term protection.…”
Section: Discussionmentioning
confidence: 99%
“…The present study has been conducted at HTD in Ho Chi Minh City since March 2021. 15 HTD is a 550-bed tertiary referral hospital for patients with infectious diseases in southern Vietnam. HTD has ∼900 members of staff and has been responsible for receiving COVID-19 patients of all severities in Southern Vietnam since the beginning of the pandemic.…”
Section: Methodsmentioning
confidence: 99%
“…The detailed descriptions about the study cohort have previously been reported. 15 In brief, a total of 554 individuals were enrolled at baseline, and 144 were selected for followed up from the second dose onward. Two doses of Oxford-AstraZeneca COVID-19 vaccine (ChAdOx1-S) were given as part of the primary course, completed by the first week of May 2021.…”
Section: Methodsmentioning
confidence: 99%
“…The detailed descriptions about the study cohort have previously been reported [15]. In brief, a total of 554 individuals were enrolled at baseline, and 144 were selected for followed up from the second dose onward.…”
Section: Methodsmentioning
confidence: 99%
“…The present study has been conducted at HTD in HCMC since March 2021 [15]. HTD is a 550-bed tertiary referral hospital for patients with infectious diseases in southern Vietnam.…”
Section: Setting and The Vaccine Evaluation Studymentioning
confidence: 99%